Peran Aktor dalam Kebijakan Retribusi pada Kawasan Taman Wisata Alam Kea-Kea - Maharani, Maharani; Sabaruddin, Abdul; Maulid, Maulid (SIGn Journal of Social Science, 2023)
This research aims to analyze the role of actors involved in the implementation of the Regent Regulation Number 7 of 2019. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that in managing retribution at the Kea-Kea Nature Tourism Park, the Department of Tourism of Kolaka Regency has played a critical role as the Policy Creator, Coordinator, and Facilitator. However, there are obstacles to policy implementation, especially in setting and collecting retribution rates and providing adequate facilities. On the other hand, Tourism Awareness Group, as the Implementer, needs help complying with the provisions for depositing the collected retribution, mainly due to using some retribution funds for facility maintenance. Furthermore, traders, acting as Accelerators, must fully comply with retribution payment regulations. Therefore, it is recommended that the Department of Tourism of Kolaka Regency enhance its effectiveness by strengthening policy socialization and implementation oversight, particularly in setting and collecting retribution rates and providing adequate facilities. For the Natural Resources Conservation Center, improving cooperation with the Department of Tourism in supervising and enforcing retribution rules is crucial. Tourism Awareness Group is expected to understand and comply with the provisions for depositing collected retribution, including the appropriate use of retribution funds. State-owned enterprises are advised to strategically allocate Corporate Social Responsibility funds to support maintaining and enhancing Kea-Kea Nature Tourism Park facilities. Finally, traders are expected to enhance compliance with retribution payment regulations. These recommendations aim to collaborate better with related actors in retribution management, ultimately improving management quality and visitor experience at the Kea-Kea Nature Tourism Park.